2014
DOI: 10.1007/s00405-014-3008-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TNF-α, OPG, IL-1β and the presence of the measles virus RNA in the stapes of the patients with otosclerosis

Abstract: Persistent measles virus infections play a crucial role in the pathomechanism of otosclerosis. The study was undertaken to investigate the role of tumor necrosis factor-α (TNF-α), interleukin 1β (IL-1β) and osteoprotegerin (OPG) in otosclerotic bone remodeling and to assess the relation of TNF-α, OPG and IL-1β expression levels in otosclerotic stape footplates to the occurrence of measles virus infection. 61 patients with otosclerosis were treated surgically. Thirty-one stapes obtained from cadavers of people,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Previous studies have suggested that decreased or missing OPG expression in OTSC tissues can be a consequence of measles virus induced inflammatory reaction which leads to increased TNF-α and IL-1β production. The increased TNF-α and IL-1β and reduced OPG levels led to an antiapoptotic effect on osteoclasts which prolonged osteoclast life and abnormal bone remodeling in the otic capsule during OTSC (Karosi et al, 2006;Potocka-Baklazec et al, 2014). Bone remodeling, however is predominantly mediated by the OPG, RANK, and RANKL system but induced by factors such as mechanical stimuli, hormones, and cytokines (Hofbauer & Heufelder, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that decreased or missing OPG expression in OTSC tissues can be a consequence of measles virus induced inflammatory reaction which leads to increased TNF-α and IL-1β production. The increased TNF-α and IL-1β and reduced OPG levels led to an antiapoptotic effect on osteoclasts which prolonged osteoclast life and abnormal bone remodeling in the otic capsule during OTSC (Karosi et al, 2006;Potocka-Baklazec et al, 2014). Bone remodeling, however is predominantly mediated by the OPG, RANK, and RANKL system but induced by factors such as mechanical stimuli, hormones, and cytokines (Hofbauer & Heufelder, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiling of disease tissue compared to controls has been suggested as a method to investigate the genetic basis of complex disorders (Xiong et al, 2012). Some of the studies have reported reduced or missing OPG expression in the otosclerotic tissue (Karosi et al, 2011;Potocka-Baklazec et al, 2014) but the exact mechanism that controls the altered OPG expression in OTSC is unclear. In this study, we aimed to identify the genetic risk factors in the OPG gene and to evaluate their potential role in OTSC development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a positive MRZ reaction (intrathecal antibody directed against 2 of 3 viruses: MV, rubella virus, and varicella-zoster virus) is considered by some to be a prognostic indicator of MS, though this test is not in widespread clinical use. Further, persistent MV infection has been speculated as a causative agent of otosclerosis (localized bone displacement resulting in hearing loss) (38)(39)(40), suggesting again that an infection acquired earlier in life can contribute to diseases that are not typically attributed a viral etiology. Finally, a link has been proposed between cytomegalovirus (CMV) and glioblastoma, as anti-CMV treatments led to a reduction in glioblastoma tumor burden (41).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, OPG knockout mice have a progressive and severe hearing loss compared to controls, as determined by ABR and DPOAE tests (7). Studies have also demonstrated that OPG levels were low in patients with otosclerosis at both the tissue and gene level (18,19). In a histopathological study conducted on 41 patients, OPG levels observed in tissue cultures were lower in patients with active otosclerosis compared to those with inactive otosclerosis (20).…”
Section: Methodsmentioning
confidence: 99%